2019
DOI: 10.1590/0104-6632.20190362s20180346
|View full text |Cite
|
Sign up to set email alerts
|

LIPIDS AS COMPETITIVE INHIBITORS OF SUBTILISIN CARLSBERG IN THE ENZYMATIC HYDROLYSIS OF PROTEINS IN RED TILAPIA (Oreochromis sp.) VISCERA: INSIGHTS FROM KINETIC MODELS AND A MOLECULAR DOCKING STUDY

Abstract: Protein hydrolysis can improve food's nutritional, techno-functional and biological properties, which can increase the possibilities of application in industry. The objective of this research article was to study the effect of lipids on the enzymatic kinetics of red tilapia viscera (RTV) hydrolysis with subtilisin Carlsberg. The RTV were hydrolyzed in an enzyme/substrate ratio of 0.153 (U/g), at 53° C, at a pH of 9.5, initial concentrations of lipids of 1, 19 and 50 g/L, and different initial substrate concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Research on the enzymatic hydrolysis of proteins in red tilapia viscera revealed that competitive inhibitors, such as lipids, may significantly compete with genuine substrates for the enzyme's active site. Conversely, non-competitive inhibitors, like certain catalysts, might cause the enzyme to alter conformation, which can impact the catalytic process as a whole [77], [78], [79].…”
Section: Competitive and Non-competitive Inhibition: A Molecular Ches...mentioning
confidence: 99%
“…Research on the enzymatic hydrolysis of proteins in red tilapia viscera revealed that competitive inhibitors, such as lipids, may significantly compete with genuine substrates for the enzyme's active site. Conversely, non-competitive inhibitors, like certain catalysts, might cause the enzyme to alter conformation, which can impact the catalytic process as a whole [77], [78], [79].…”
Section: Competitive and Non-competitive Inhibition: A Molecular Ches...mentioning
confidence: 99%